A Lethal Case of DEET Toxicity Due to Intentional Ingestion. (6th July 2014) - Wiles, Devin; Yee, Justin; Castillo, Uvidelio; Russell, Jason; Spiller, Henry; Casavant, Marcel
Abstract: A 37-year-old male with prior medical history of profound developmental delay experienced seizure and cardiac arrest following ingestion of 6 ounces of a 40% N, N -diethyl- meta -toluamide (DEET) containing solution. The patient was unresponsive, acidemic, tachycardic and hypotensive on presentation. Over three hospital days, the patient's vitals recovered to baseline but he remained unresponsive and areflexic with fixed and dilated pupils. Non-contrast brain magnetic resonance imaging showed cerebral edema, transtentorial and tonsillar herniations. A rapid, simple and sensitive high-performance liquid chromatography (HPLC) method was utilized for the analysis of postmortem plasma blood and urine samples of a lethal case of DEET intentional ingestion. The method combined the use of C18 SepPak cartridges for solid phase extraction and reversed-phase HPLC. One urine and five blood samples from this patient were analyzed for DEET concentration. Mixtures of serum/urine postcentrifuge were eluted and reduced to 1 mL using a solvent evaporator. Blood in ethylenediaminetetraacetic acid (EDTA), whole blood, serum, blood with heparin and urine DEET concentrations were 9.84, 9.21, 10.18, 8.66dl and 0.642 mg/dL, respectively. All samples were collected <1 h postingestion. Although seizures and cardiac toxicity have been described in other case reports, this case is atypical due to the exceptional dose ingested and the timing of the fluid test samples being drawn so soon following exposure. Although a widely used and extremely safe insect repellent, DEET can be highly toxic in large but easily obtainable doses.